Risk Prediction Models and Scores in Hypertrophic Cardiomyopathy - Gossios, Thomas D.; Savvatis, Konstantinos; Zegkos, Thomas; Parcharidou, Despina; Karvounis, Haralambos I.; Efthimiadis, Georgios K. (Current Pharmaceutical Design, 2021)
Hypertrophic cardiomyopathy (HCM) has historically been linked with sudden cardiac death (SCD). Currently, it is well established that only a subset of patients is at the highest risk stratum for such a catastrophic event. Detection of patients belonging to this high-risk category can allow for timely defibrillator implantation, changing the natural history of HCM. Inversely, device implantation in patients deemed at low risk leads to an unnecessary burden of device complications with no apparent protective benefit. Previous studies have identified a series of markers, now considered established risk factors, with genetic testing and newer imaging allowing for the detection of novel, highly promising indices of increased risk for SCD. Despite the identification of a number of risk factors, there is noticeable discrepancy in the utility of such factors for risk stratification between the current American and European guidelines. We sought to systematically review the data available on these two approaches, presenting their rationale and respective predictive capacity, also discussing the potential of novel markers to augment the precision of currently used risk stratification models for SCD in HCM.
Keywords: sudden death